). Pengaruh Kemampuan Menyusun Laporan Keuangan, Literasi Keuangan, Dan Financial Technology Terhadap Kinerja UMKM - Ade Puspita, Reni Suwandi; Gurendrawati, Etty; Ulupui, I Gusti Ketut Agung (LPPM Universitas Negeri Jakarta, 2024)
This quantitative research aims to determine how the ability to compile financial statements, financial literacy, and financial technology affects MSMEs. The main data for this study came from questionnaires, research instruments. MSME owners who live in Matraman District and are registered with the East Jakarta Small and Medium Enterprises Cooperative Trade Industry Office (Sudin PPKUKM) are the subjects of this study. This study gathered 59 MSMEs using the Roscoe method. To analyze the data, multiple linear analysis was carried out using the SPSS program version 26, and from the results of the analysis it can be concluded that the variable ability to compile reports does not affect the performance of MSMEs, financial literacy does not affect the performance of MSMEs, and financial technology does not affect the performance of MSMEs.